2020
DOI: 10.1155/2020/4657151
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Error Variance-Covariance Parameters Using Multivariate Geographically Weighted Regression Model

Abstract: The Multivariate Geographically Weighted Regression (MGWR) model is a development of the Geographically Weighted Regression (GWR) model that takes into account spatial heterogeneity and autocorrelation error factors that are localized at each observation location. The MGWR model is assumed to be an error vector ε that distributed as a multivariate normally with zero vector mean and variance-covariance matrix Σ at each location ui,vi, which Σ is sized qxq for samples at the i-location. In this study, the estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Ordinary least squares (OLS) regression models are nonspatial models and the most representative linear regression models were used to initially explain the complex relationship between the built environment and subway capacity [15,35,36], which assumes that the relationship between independent variables and the dependent variable is global and not spatially heterogeneous. In terms of spatial models, among the most common are spatial error models [37,38], spatial lag models [39], geographically weighted regression models [32,40,41], and derivative models related to geographically weighted regression models, such as geographic time-weighted regression (GTWR) models [42], geographically weighted negative binomial regression (GWNBR) models [43], geographically weighted Poisson regression (GWPR) models [44], and mixed geographically weighted regression (MGWR) models [13,18,45]. For example, Li et al [32] used a GWR model to refine the study of Guangzhou Subway.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ordinary least squares (OLS) regression models are nonspatial models and the most representative linear regression models were used to initially explain the complex relationship between the built environment and subway capacity [15,35,36], which assumes that the relationship between independent variables and the dependent variable is global and not spatially heterogeneous. In terms of spatial models, among the most common are spatial error models [37,38], spatial lag models [39], geographically weighted regression models [32,40,41], and derivative models related to geographically weighted regression models, such as geographic time-weighted regression (GTWR) models [42], geographically weighted negative binomial regression (GWNBR) models [43], geographically weighted Poisson regression (GWPR) models [44], and mixed geographically weighted regression (MGWR) models [13,18,45]. For example, Li et al [32] used a GWR model to refine the study of Guangzhou Subway.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Harini et al [1,2] introduced the multivariate GWR (MGWR) model and demonstrated the parameter estimation and hypothesis test procedures using the restricted maximum likelihood estimation (RMLE) and maximum likelihood ratio test (MLRT) methods, respectively. The form and properties of the estimated errors variance-covariance parameters of the MGWR model using the MLE and weighted least squares methods were investigated [3]. Triyanto et al [4,5] introduced the geographically weighted multivariate Poisson regression (GWMPR) model.…”
Section: Introductionmentioning
confidence: 99%